2002
DOI: 10.1007/s00216-002-1265-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of modern sample-preparation techniques for the extraction and analysis of medicinal plants

Abstract: Sample preparation is the crucial first step in the analysis of herbs. In recent years there has been increasing interest worldwide in the use of alternative/herbal medicine for the prevention and treatment of various illnesses. Currently, however, quality-related problems (lack of consistency, safety, and efficacy) seem to be overshadowing the potential genuine health benefits of various herbal products. Thus, the development of "modern" sample-preparation techniques with significant advantages over conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
277
0
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(289 citation statements)
references
References 51 publications
1
277
0
11
Order By: Relevance
“…Recently, studies have demonstrated the use of micellar media as an alternative to organic solvent for extracting organic pollutants from solid environmental samples [21][22][23][24]. Moreover, Huie [25,26] and Ong [27,28] proved that the surfactant solutions in ASE can effectively extract the active ingredients in medicinal plants, and avoid the degradation of thermally unstable ingredients at high temperature. To the best of our knowledge, the reports on the use of environmental friendly surfactant solutions in ASE of PAHs from soil are rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have demonstrated the use of micellar media as an alternative to organic solvent for extracting organic pollutants from solid environmental samples [21][22][23][24]. Moreover, Huie [25,26] and Ong [27,28] proved that the surfactant solutions in ASE can effectively extract the active ingredients in medicinal plants, and avoid the degradation of thermally unstable ingredients at high temperature. To the best of our knowledge, the reports on the use of environmental friendly surfactant solutions in ASE of PAHs from soil are rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors such as solvent characteristic, extraction time, temperature, and ratio of sample to solvent have an influence on extraction 11 . In this experiment, we selected ethanol as a solvent followed the work of Chen et al 8 because the crude extract of PL contains effective component in an anti-cancer test.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrated extracts were then placed on watch glass and heated, 40 °C, to speed the evaporation of solvents. Finally, dried extracts of the plants were obtained [25][26][27][28].…”
Section: 2mentioning
confidence: 99%